Weight Gain, Obesity, and Psychotropic Prescribing - Nikhil Nihalani; Thomas L. Schwartz; Umar A. Siddiqui; James L. Megna (Journal of Obesity)
A majority of psychiatric medications are known to generate weight gain and ultimately obesity in some patients. There is much speculation about the prevalence of weight gain and the degree of weight gain during acute and longitudinal treatment with these agents. There is newer literature looking at the etiology of this weight gain and the potential treatments being used to alleviate this side effect. The authors undertook a comprehensive literature review in order to present epidemiology, etiology, and treatment options of weight gain associated with antipsychotics, mood stabilizers, and antidepressants.